Computational fluid dynamics evaluation of pig house ventilation systems for improving the internal rearing environment. (October 2019) - Yeo, Uk-Hyeon; Lee, In-Bok; Kim, Rack-Woo; Lee, Sang-Yeon; Kim, Jun-Gyu
Abstract : Due to the cold stress experienced by pigs, and the increased energy load during winters and the changes from winter to spring and summer to autumn, it is difficult to provide sufficient ventilation in pig houses. These factors can result in a poor internal environment. Therefore, fundamental measures to increase the ventilation rate and a corresponding analysis of the effects were needed to improve internal rearing environment. Due to the characteristics of invisible air, it was difficult to analyse the aerodynamic characteristics inside a pig house by field experiment. Computational fluid dynamics (CFD) has been used to overcome such limitations for the last 30 years. In this study, environmental monitoring (air temperature, humidity, etc.) in a commercial pig house were conducted to identify environmental problems. After this, CFD validated models were designed and evaluated to find effective solutions, by changing the conditions of the pig house air inlets and outlets (air buffer space, inlet duct, and exhaust fan). Compared with the conventional ventilation system of the experimental pig house, adjusting the hole spacing of the inlet duct and installing a roof–chimney exhaust fan did not significantly improve the rearing environment. However, when an air buffer space was installed just before the location of the inlet on the sidewall, the air temperature flowing through the air buffer space increased making it possible to supply more than twice the external air to the pig house, while maintaining the air temperature distribution at the height of the animal-occupied zone. Highlights: The evaluation of ventilation systems of a pig house was conducted using CFD. Most efficient predicted solution was applied to an experimental pig house. The effect of the design was validated.